BCM673: Project evaluation and development / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2018)
This course introduces the objectives of development management knowledge which are essential during work as a professional manager in realising a commercially viable project. The course covers project appraisal, development a design concept, finance, construction methods, post construction methods, post construction and oocupancy evaluation and maintenance